2002
DOI: 10.1016/s1097-2765(02)00522-1
|View full text |Cite
|
Sign up to set email alerts
|

E2F1 and c-Myc Potentiate Apoptosis through Inhibition of NF-κB Activity that Facilitates MnSOD-Mediated ROS Elimination

Abstract: Overexpression of c-Myc or E2F1 sensitizes host cells to various types of apoptosis. Here, we found that overexpressed c-Myc or E2F1 induces accumulation of reactive oxygen species (ROS) and thereby enhances serum-deprived apoptosis in NIH3T3 and Saos-2. During serum deprivation, MnSOD mRNA was induced by NF-kappaB in mock-transfected NIH3T3, while this induction was inhibited in NIH3T3 overexpressing c-Myc or E2F1. In these clones, E2F1 inhibited NF-kappaB activity by binding to its subunit p65 in competition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
207
6
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(239 citation statements)
references
References 37 publications
20
207
6
3
Order By: Relevance
“…E2F competes with the p50 subunit of NF-kB resulting in NF-kB inactivation. Inactivation of NF-kB decreased MnSOD transcription, which could then result in increased ROS levels (Tanaka et al, 2002). These results further support the threshold concept of ROS function; lower levels of ROS are growth stimulatory, whereas higher levels of ROS are detrimental.…”
Section: Intracellular Redox State and Cell Cycle Proteinssupporting
confidence: 75%
See 1 more Smart Citation
“…E2F competes with the p50 subunit of NF-kB resulting in NF-kB inactivation. Inactivation of NF-kB decreased MnSOD transcription, which could then result in increased ROS levels (Tanaka et al, 2002). These results further support the threshold concept of ROS function; lower levels of ROS are growth stimulatory, whereas higher levels of ROS are detrimental.…”
Section: Intracellular Redox State and Cell Cycle Proteinssupporting
confidence: 75%
“…As discussed earlier, entry into the S phase is preceded by a transient increase in prooxidant levels (Menon et al, 2003), which is consistent with a decrease in MnSOD activity in the S phase (Li and Oberley, 1998). However, persistent increase in E2F is deleterious and induces apoptosis in serumstarved NIH3T3 fibroblasts (Tanaka et al, 2002). E2F overexpression-induced apoptosis is associated with increased ROS levels and inactivation of MnSOD transcription.…”
Section: Intracellular Redox State and Cell Cycle Proteinssupporting
confidence: 57%
“…Further, LMPIP may shorten G1/S transition through a decrease in pocket protein (RB) expression. Many studies also showed oxidative stress decreased RB phosphorylation, which blocked E2F1 release and the activation of G1/S regulators (Esposito et al, 2001;Tanaka et al, 2002). In this study, it was found that in LMPIP-transfected NPC cells, cyclin D and CDK were activated and higher levels of E2F1 expression were also detected, with concurrent decrease in RB expression.…”
Section: Discussionsupporting
confidence: 51%
“…For example, well-described oncogenes such as Myc, Ras, and E2F1, which deliver strong mitogenic signals, have also been reported to cause cell death. 33,34 In addition, insulin-like growth factor, which is a well-known mitogenic and antiapoptotic factor for many cells, was proven to significantly inhibit DNA synthesis and cell proliferation in a human lung adenocarcinoma cell line, possibly via the sustained activation of AKT1 and the induction of p21. 35 Therefore, it is possible that the outcome of AKT1 activation may vary depending on the type of stimulus and the microenvironment, or activated AKT1 may direct signals in an organ (or tumor)-specific manner.…”
Section: Discussionmentioning
confidence: 99%